2022
DOI: 10.3390/agronomy12092109
|View full text |Cite
|
Sign up to set email alerts
|

Did Wheat Breeding Simultaneously Improve Grain Yield and Quality of Wheat Cultivars Releasing over the Past 20 Years in China?

Abstract: Grain yield and quality of wheat are both important components for food security. Great effort has been made in the genetic improvement of wheat grain yield in China. However, wheat grain quality (i.e., protein concentration and protein quality) has received much less attention and is often overlooked in efforts to improve grain yield. A timely summary of the recent process of wheat breeding for increasing yield and quality (which can be used to guide future breeding strategies) is essential but still lacking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The GG obtained was within the range reported in Spain (0.88% yr -1 from 1931 to 2000) (Sanchez-Garcia et al, 2013), and France (0.66% yr -1 from 1962 to 1988) (Brancourt-Hulmel et al, 2003). Other studies reported higher values of GG, ranging from 1.1% yr -1 in the United States Central Plains from 1903 to 2014 (Rife et al, 2019) to 1.17% yr -1 in Argentina from 1940 to 1999 (Lo Valvo et al, 2018) and 1.29% yr -1 in China during the period of 1950-2015 (Hu et al, 2022). J. N. Cobb et al (2019) reported that most public wheat breeding programs realized less than 1% of GG over the last 30 years.…”
Section: Genetic Gains For Grain Yieldmentioning
confidence: 92%
See 2 more Smart Citations
“…The GG obtained was within the range reported in Spain (0.88% yr -1 from 1931 to 2000) (Sanchez-Garcia et al, 2013), and France (0.66% yr -1 from 1962 to 1988) (Brancourt-Hulmel et al, 2003). Other studies reported higher values of GG, ranging from 1.1% yr -1 in the United States Central Plains from 1903 to 2014 (Rife et al, 2019) to 1.17% yr -1 in Argentina from 1940 to 1999 (Lo Valvo et al, 2018) and 1.29% yr -1 in China during the period of 1950-2015 (Hu et al, 2022). J. N. Cobb et al (2019) reported that most public wheat breeding programs realized less than 1% of GG over the last 30 years.…”
Section: Genetic Gains For Grain Yieldmentioning
confidence: 92%
“…The wheat yield exhibited a continuous positive increase: from 2.57 t ha -1 in 1980-1990 to 3.28 t ha -1 in 2013-2022. This means that the new released cultivars are a key for improving yields, especially that more than half of the test environments used for the analysis faced severe to moderate drought (Hu et al, 2022). The significant average annual genetic gain (GG) in GY since 1980 was found to be 21.4 kg yr -1 (0.75%/year), establishing the efficient contribution of breeding activities carried out in the last four decades towards improving the wheat yields in Morocco.…”
Section: Genetic Gains For Grain Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research perspective differs from that of previous scholars. Most scholars have studied the key factors affecting staple food quality from the perspective of natural sciences (Randhe et al, 2009), such as breeding science (Hu et al, 2022), sowing methods (Pearsons et al, 2022;Zhu et al, 2022), production and inputs (Randhe et al, 2009;Ali and Akmal, 2022), growth environment (Kim and Kim, 2021;Zahra et al, 2023) and processing (Peng et al, 2022). Nevertheless, it is not enough to study staple food quality only from the physical and chemical properties.…”
Section: Discussmentioning
confidence: 99%
“…China has made remarkable achievements in the breeding and production of wheat varieties in recent years [ 17 ], but the production of frozen dumplings is still in need of wheat flours of higher quality. Meanwhile, with the development of the economy and society, citizens’ eating habits have become more diversified, and multi-level requirements for pastas have occurred.…”
Section: Introductionmentioning
confidence: 99%